An Analysis of Higher Order Thinking Skills in English Textbook Exercises for Senior High School - Pare, Syelin Nathan; Suhartini, Lelly; Rohmana, Rohmana (Universitas Halu Oleo, 2021)
The research was conducted to analyze the use of Higher Order Thinking Skills in English textbook exercises for senior high school. The scope was focused on three skills; analyze, evaluate and create that exist on reading exercises of English textbook â€œBahasa Inggris Kelas X SMA/MA/SMK/MAKâ€. The research used desk research while the instrument used guideline according to Bloomâ€™s Taxonomy Revised. Technique of data analysis consisted of data reduction, data display, and conclusion drawing/verification. The result showed that from 168 reading exercises, 9 exercises were classified into analyze (C4), 5 exercises were classified into evaluate (C5) and 2 exercises were classified into create (C4). This meant that from 168 reading exercises in English textbook, 16 exercises were classified into higher order thinking skills, with the frequency of question 56,25% Analyze (C4), 31,25% Evaluate (C5) and 12,5% Create (C6). Therefore, findings indicated that higher order thinking skills in English textbook reading exercises was still low.